Flexoelectricity, Triboelectricity, and Free Interfacial Charges - Marks, L. D.; Olson, K. P. (Small (Weinheim an der Bergstrasse, Germany), 2025)
Triboelectricity has been a topic of some confusion for many years, probably because it is very diverse and some of the fundamental science has not been clear. This is now starting to change. A few years ago, the importance of flexoelectricity at asperities is pointed out. That paper exploited the established physics of compensation of bound surface or interfacial charges without going into detail. The purpose of this paper is to expand further on this, mapping from the established physics of electrostatics with contact potentials and Maxwell's displacement field to the underlying fundamentals of charge transfer in triboelectricity. Examples from the published literature are used to illustrate this. In the discussion, some of the open questions and challenges to the community are mentioned. What is observed macroscopically for triboelectric charging as shown on the left involves polarization, bound surface charges, and free charges as shown on the right.